Eight years of homicide evolution in Monterrey, Mexico: a network approach - Dorantes-Gilardi, Rodrigo (2020)
Homicide is without doubt one of Mexico's most important security problems, with data showing that this dismal kind of violence sky-rocketed shortly after the war on drugs was declared in 2007. Since then, violent war-like zones have appeared and disappeared throughout Mexico, causing unfathomable human, social and economic losses. One of the most emblematic of these zones is the city of Monterrey, a central scenario in the narco-war. To better understand the underlying mechanisms by which violence has evolved and spread through the city, here we propose a network-based approach. For this purpose, we define a homicide network where nodes are geographical entities that are connected through spatial proximity and crime similarity. Data is taken from a crime database spanning 86 months in the Monterrey metropolitan area, containing manually curated geo-located and dated homicides, as well as from Open Street Map for urban environment. Under this approach, we first identify independent crime sectors corresponding to different connected components. Each of these clusters of crime presents crime evolution similar to the one at state and national levels. We then show how crime spread from neighborhood to adjacent neighborhoods when violence was mainly cartel-related and how it was chiefly static at a different time. Finally, we show a relation between homicidal crime and urban landscape by studying the distance of safe and violent neighborhoods to the closest highway and by studying the evolution of highway and crime distance over the cartel-related years and the following period. With this approach, we are able to describe more accurately the evolution of homicidal crime in a metropolitan area